2019
DOI: 10.1002/jsfa.10041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an angiotensin‐I‐converting enzyme inhibitory peptide from tilapia (Oreochromis niloticus) with captopril: inhibition kinetics, in vivo effect, simulated gastrointestinal digestion and a molecular docking study

Abstract: BACKGROUND: In order to utilize tilapia skin gelatin hydrolysate protein, which is normally discarded as industrial waste in the process of fish manufacture, we study the in vivo and in vitro angiotensin-I-converting enzyme (ACE) inhibitory activity of the peptide Leu-Ser-Gly-Tyr-Gly-Pro (LSGYGP). The aim was to provide a pharmacological basis of the development of minimal side effects of ACE inhibitors by comparative analysis with captopril in molecular docking. RESULTS:This peptide from protein-rich wastes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Molecular docking has shown the potential of these peptides as ACE inhibitors with potential use in preparation of functional food targeted at lowering blood pressure and reducing the risk of CVDs [ 161 ]. The same result was reported for the IVDR, WYK, and VSAVI peptides obtained from olive flounder ( P. olivaceus ) surimi [ 175 ] and the LSGYGP peptide obtained from tilapia ( O. niloticus ) skin gelatin protein hydrolysate [ 176 ]. The LWHTH peptide obtained from the tunicate ( S. clava ) in in silico simulations was found to bind to the active site of ACE, making the ACE–LWHTH complex stable.…”
Section: New Alternative Sources Of Peptidessupporting
confidence: 78%
“…Molecular docking has shown the potential of these peptides as ACE inhibitors with potential use in preparation of functional food targeted at lowering blood pressure and reducing the risk of CVDs [ 161 ]. The same result was reported for the IVDR, WYK, and VSAVI peptides obtained from olive flounder ( P. olivaceus ) surimi [ 175 ] and the LSGYGP peptide obtained from tilapia ( O. niloticus ) skin gelatin protein hydrolysate [ 176 ]. The LWHTH peptide obtained from the tunicate ( S. clava ) in in silico simulations was found to bind to the active site of ACE, making the ACE–LWHTH complex stable.…”
Section: New Alternative Sources Of Peptidessupporting
confidence: 78%
“…Chen et al. (2020) also separated a novel ACE inhibitory peptide in a sequence of LSGYGP from gelatin hydrolysate protein of tilapia skin, and its IC 50 was 2.577 µmol/L. Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotensive effects have been observed upon treatment with isolated fractions of plant extracts, mainly associated with the presence of compound antioxidants, saponins and peptides [ 17 , 24 , 30 ]. The mode of action of the inhibitory effect is proposed to be the interaction of antioxidant molecules with different motifs on the ACE catalytic site [ 28 ], specifically, the union of these compounds with the zinc atom present in the catalytic site of ACE, as described by Reeves and Rossow [ 31 ]. EESH has been known to contain a high content of antioxidant compounds (chlorogenic acid, caffeic acid, myricetin, quercetin and kaempferol) [ 18 ], implying that the inhibitory effect of Salvia extracts could be attributed to the presence of antioxidants compounds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Steinkamp-Fenske et al [ 21 ] and Zhou et al [ 32 ] analyzed the effect of administration of S. milthiorriza extracts on the regulation and production of NO in a human umbilical endothelium-derived cell line. The authors found a concentration-dependent response besides an over-regulation of eNOS in the treated cells, as compared to control cells [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. We analyzed genes coding for proteins that participate in three different pathways involved in regulation of HT, namely renin–angiotensin system ( Ace and Agtr1a genes), the kallikrein–kinin system ( Bdkrb2 gene) and the nitric oxide ( Nos3 gene) synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%